Borohydride as Magnetic Superexchange Pathway in Late Lanthanide Borohydrides. Issue 13 (14th March 2019) - Wegner, Wojciech; van Leusen, Jan; Majewski, Jacek; Grochala, Wojciech; Kögerler, Paul
Abstract : The magnetic characteristics of a series of borohydride‐based systems, including binary α‐/β‐Ln(BH4 )3 phases (Ln = Gd, Tb, Dy, Ho, Er, and Tm) with direct Ln–HBH–Ln bridges and selected mixed‐metal systems, LiYb(BH4 )4, NaYb(BH4 )4, KHo(BH4 )4, RbTm(BH4 )4, with isolated Ln 3+ ions embedded in [Ln(BH4 )4 ] – anions are described for the first time using SQUID magnetometry and DFT+U calculations. Crystal field effects as well as the nature and strength of magnetic superexchange interactions via BH4 – ligands are established based on a ligand field theory approach. We find Auzel's scalar crystal field strength parameter ( Nv, the weighted quadratic mean of the ligand field parameters Bk q ) for these systems to be substantial, in particular for α‐Ho(BH4 )3, indicating a significant covalent component in the Ho··· H bonding. The BH4 – anion is capable of mediating both weakly ferro‐ or antiferromagnetic superexchange. Quantum mechanical DFT+U calculations, even when including spin‐orbit coupling effects, do not reliably describe the sign and the size of the magnetic superexchange constants in these systems. Abstract : In contrast to its "smaller brother", the hydride anion, BH4 – can transmit both ferromagnetic and antiferromagnetic coupling in lanthanide‐based borohydride phases, due to the crucial role of the boron 2p orbitals that are involved in the superexchange. In Ho 3+, very high ligand field splitting is observed, suggesting a pronounced covalent component in Ho–H(BH3 ) bonds.